Investigating the effects of blended sulphated polysaccharide fucoidan in alginate hydrogel on the chondrogenic diffrentiation potential of mesenchymal sromal cells: In vitro and vivo study / Puvanan Karunanithi - Puvanan, Karunanithi (2017)
Presence of sulphated polysaccharides has often been implicated in the regulation of chondrogenesis. The present study was undertaken to investigate the potential of fucoidan, a natural sulphated polysaccharide extracted from seaweeds, in enhancing the chondrogenic differentiation of mesenchymal stromal cells encapsulated in alginatefucoidan (Al-Fu) hydrogel in vitro and their potential in the repair of full thickness chondral defects created in a rabbit model in vivo. A composite alginate-fucoidan (Al-Fu) hydrogel consisting of alginate (1.5%) artd fucoidan (0.5%) was fabricated. For the in vitro study, human mesenchymal stromal cells (hMSC) were encapsulated in alginatefucoidan (Al-Fu) hydrogel or alginate (Al) hydrogel alone. These hydro gels were cultured in medium supplemented with either FBS or chondrogenic differentiation inducing supplements. Ability of Al-Fu to support hMSC chondrogenic differentiation was confirmed after 7, 14 and 21 days of culture. For the in vivo study, chondral defects (5mm) were created in both the knees of eighteen mature New Zealand white rabbits using custom-made cylindrical chondrotome in the non-contiguous medial condyle. After one month, rabbits were randomly divided into three groups containing 3 animals each. The right knees were transplanted with rabbit MSCs (rbMSCs) encapsulated in AI hydrogel (Group I), rbMSCs encapsulated in Al-Fu hydrogel (Group II), and Al-Fu hydrogel alone (Group III). The left knees received no treatment and served as the control. After 3 and 6 months post-transplantation, all animals were sacrificed and the augmentation in cartilage repair was assessed. Fucoidan incorporation improved the chondrogenesis of hMSCs. This was demonstrated by increased expression of cartilage extracellular matrix specific genes such as collagen type II, aggrecan, SOX9 and COMP in hMSC encapsulated in AlFu hydrogel. Meanwhile the expression of hypertrophic genes collagen X and RUNX2 were downregulated in cells encapsulated in the Al-Fu hydrogel. These results were further confirmed by the higher synthesis of glycosaminoglycan, stronger immunocytochemical staining and higher protein synthesis of cartilage extracellular matrix proteins such as collagen type II, aggrecan and COMP in cells encapsulated in AlFu hydrogel. The in vivo results demonstrated the formation of a hyaline-like repair tissue in defects site that were transplanted with rbMSCs encapsulated in AI (Group I) and rbMSCs encapsulated in Al-Fu hydrogels (Group II). This was confrrmed by ICRS, O'Driscoll scores and histological staining of the regenerated tissues. The highest ICRS scorings was observed in group II, while the lowest score was observed in group III. O'Driscoll scores for the repair tissue was significantly high in Group II (p<0.05). Immunohistochemical staining for collagen type II showed intense staining in Group II compared to the other groups. Glycosaminoglycan content was also significantly higher (p<0.05) in group II as compared to groups I and III. Hence, fucoidan can be used as a promising additive to drive efficient cartilage repair. Fucoidan incorporation enhanced the chondrogenesis and also decreased the cell hypertrophy in vitro. Altogether, this study suggests that fucoidan could be used for fabricating a bio-composite hydrogel for the potential repair of cartilage defects in cartilage tissue engineering applications.